Five articles by various authors on Fenianism in the Cork area, - Ó Muirthile, Séan.
Includes 'Ned Kelly' and 'Billy O'Shea' by Seán Ó Muirthile and 'Fenianism - Cork and Limerick in 1867' by Jim Hurley.